2020
DOI: 10.1016/j.it.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Heterogeneity of Human Dendritic Cell Subsets

Abstract: Dendritic cells (DCs) have been classified into distinct subsets based on phenotype and ontogeny. In the past few years, high throughput single-cell approaches have revealed further heterogeneity of human DCs, in particular at the transcriptomic level. Herein examined, are recent studies describing new human DC populations based on single-cell RNA-seq analysis, and a unified view of these emerging DC populations is presented. Also assessed are the features that define bona fide DC lineages, as opposed to cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 65 publications
4
75
0
Order By: Relevance
“…We showed that CD14 + CD1c + cells as well as other cDCs, primed and promoted the proliferation of naïve CD4 + T cells at higher levels than did monocytes (Figure 2C), supporting a distinct functionality of CD14 + CD1c + cells from macrophages. Moreover, it is difficult to distinguish between DC3s and MoDCs because their functionality and transcription profiles tend to overlap conspicuously and no discriminative markers have been reported yet (13). However, our transcriptional analysis demonstrated that CD14 + CD1c + cells isolated from hNOJ mice are closer to cDC2s and DC3s than to MoDCs in humans (Supplementary Figure 4).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We showed that CD14 + CD1c + cells as well as other cDCs, primed and promoted the proliferation of naïve CD4 + T cells at higher levels than did monocytes (Figure 2C), supporting a distinct functionality of CD14 + CD1c + cells from macrophages. Moreover, it is difficult to distinguish between DC3s and MoDCs because their functionality and transcription profiles tend to overlap conspicuously and no discriminative markers have been reported yet (13). However, our transcriptional analysis demonstrated that CD14 + CD1c + cells isolated from hNOJ mice are closer to cDC2s and DC3s than to MoDCs in humans (Supplementary Figure 4).…”
Section: Discussionmentioning
confidence: 83%
“…However, differences in phenotypes and functionalities exist in the same DC subsets between humans and mice (8)(9)(10)(11)(12). Furthermore, there is a new DC subset in humans, DC3s, whose equivalent counterparts have not yet been identified in mice (13). Thus, it is valuable to establish animal models that precisely reproduce human DC subsets, as they can prove useful for translational research where DCs are utilized for immunotherapy against cancer and infectious diseases (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, characterising these populations and understanding their functions under different conditions will be important for improving the treatment of disease and for developing preventative strategies, such as vaccines. However, this has proved difficult due to the expression of overlapping phenotypic markers and due to the heterogeneity within each subset, which is becoming increasingly evident (Brown et al, 2019; Dutertre et al, 2019; Guilliams et al, 2016; Villar and Segura, 2020). This is particularly so in non-lymphoid tissues such as the intestine, where local factors imprint unique adaptations and functions, meaning that each tissue has to be explored independently and at the single-cell level (Blériot et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic cells ( DCs ). DCs are a diverse group of specialized antigen-presenting cells (APCs) playing a central role in inducing primary immune responses, immunological tolerance and ensuring the regulation of responses of T cells [ 248 ]. Although DCs constitute a rare immune cell population within tumors and lymphoid organs, these cells are central to initiation and tumor immunity [ 249 ].…”
Section: The Endocannabinoid System As Gate-keeper Of the Immune Systemmentioning
confidence: 99%